Tolerance development in cow's milk–allergic infants receiving amino acid–based formula: A randomized controlled trial - Pantipa Chatchatee (2022)
Background: Tolerance development is an important clinical outcome for infants with cow's milk allergy. Objective: This multicenter, prospective, randomized, double-blind, controlled clinical study (NTR3725) evaluated tolerance development to cow's milk (CM) and safety of an amino acid–based formula (AAF) including synbiotics (AAF-S) comprising prebiotic oligosaccharides (oligofructose, inulin) and probiotic Bifidobacterium breve M-16V in infants with confirmed IgE-mediated CM allergy. Methods: Subjects aged ≤13 months with IgE-mediated CM allergy were randomized to receive AAF-S (n = 80) or AAF (n = 89) for 12 months. Stratification was based on CM skin prick test wheal size and study site. After 12 and 24 months, CM tolerance was evaluated by double-blind, placebo-controlled food challenge. A logistic regression model used the all-subjects randomized data set. Results: At baseline, mean ± SD age was 9.36 ± 2.53 months. At 12 and 24 months, respectively, 49% and 62% of subjects were CM tolerant (AAF-S 45% and 64%; AAF 52% and 59%), and not differ significantly between groups. During the 12-month intervention, the number of subjects reporting at least 1 adverse event did not significantly differ between groups; however, fewer subjects required hospitalization due to serious adverse events categorized as infections in the AAF-S versus AAF group (9% vs 20%; P = .036). Conclusions: After 12 and 24 months, CM tolerance was not different between groups and was in line with natural outgrowth. Results suggest that during the intervention, fewer subjects receiving AAF-S required hospitalization due to infections.